A comprehensive review of the relationship between autophagy and sorafenib-resistance in hepatocellular carcinoma: ferroptosis is noteworthy - Zhang, Kangnan; Zhang, Qinghui; Jia, Rongrong; Xiang, Shihao; Xu, Ling (Frontiers in Cell and Developmental Biology, 2023)
Patients with hepatocellular carcinoma (HCC) bear heavy burden of disease and economy but have less treatment options. Sorafenib, as a multi-kinase inhibitor, is the only approved drug that be used to limit the inoperable or distant metastatic HCC progression. However, enhanced autophagy and other molecular mechanisms after sorafenib exposure further induced drug resistance in HCC patients. Sorafenib associated autophagy also generated a series of biomarkers, which may represent that autophagy is a critical section of sorafenib-resistance in HCC. Furthermore, many classics signaling pathway have been found be involved in sorafenib associated autophagy, including HIF/mTOR signaling pathway, endoplasmic reticulum stress, and sphingolipid signaling, etc. In turn, autophagy also provokes autophagic activity in components of the tumor microenvironment including tumor cells and stem cells, further impacting sorafenib-resistance in HCC through a special autophagic cell death process (ferroptosis). In this review, we summarized the latest research progress and molecular mechanisms of sorafenib-resistance-associated autophagy in detail, to provide new insights and ideas for unraveling the dilemma of sorafenib-resistance in HCC.